Evaluation of fusarium head blight resistance through a genome-wide association study in CIMMYT and South Asian wheat germplasm - Mandal, Rupsanatan; Xinyao He; Singh, Gyanendra Pratap; Kabir, Muhammad Rezaul; Joshi, Arun Kumar; Pawan Kumar Singh (MDPI, 2025)
Fusarium head blight (FHB) is an important disease throughout the world due to its strong association with yield reduction, quality deterioration, and mycotoxin contamination in wheat. The use of FHB-resistant genotypes in wheat production can significantly reduce damage. The current study screened a panel of bread wheat from CIMMYT and South Asian countries for FHB resistance to identify promising genotypes useful for wheat breeding and to map the associated genomic regions and linked molecular markers through a genome-wide association study (GWAS). Spray-inoculated field experiments were conducted at CIMMYT, Mexico, over three years, and a wide range of phenotypic variations was observed. Four lines, CIM-39, CIM-29, CIM-9, and CIM-3, exhibited consistent resistance across experiments, with FHB indices ranging from 6.5 to 8.1. Genotyping was conducted using the Illumina Infinium 15 K Bead Chip, and 11,184 high-quality SNP markers were obtained and used for GWAS. Nineteen significant marker-trait associations (MTAs) were detected, among which MTAs at Ra_c58315_265 on 1A and Tdurum_contig102328_129 and Ku_c20136_198 on 7B showed reproducible results, with phenotypic effects on FHB resistance of 6.05%, 3.54%, and 3.92%, respectively. Several genes associated with disease resistance were found near the significant SNPs. The identified resistant genotypes and markers may be useful in future marker-assisted breeding in wheat.